2016
DOI: 10.1002/bies.201600093
|View full text |Cite
|
Sign up to set email alerts
|

Random sex determination: When developmental noise tips the sex balance

Abstract: Sex-determining factors are usually assumed to be either genetic or environmental. The present paper aims at drawing attention to the potential contribution of developmental noise, an important but often-neglected component of phenotypic variance. Mutual inhibitions between male and female pathways make sex a bistable equilibrium, such that random fluctuations in the expression of genes at the top of the cascade are sufficient to drive individual development toward one or the other stable state. Evolutionary m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 100 publications
1
45
0
Order By: Relevance
“…Altogether, these recent data confirmed that at least in these lineages TSD and GSD are not mutually exclusive systems but the 2 extreme endpoints of a continuum, underlying the coexistence of both genetic and environmental influences in the middle of this spectrum: 'many species have differentiated sex chromosomes, but also show a temperature override, where genes and environment interact to determine sex' [Holleley et al, 2015]. In fact just recently, a three-ended continuum that can be visualized as a triangle has been proposed [Perrin, 2016] in which genes, environment, and random factors (i.e., any stochastic fluctuation in the expression of key genes of the cascade) could interact to determine sex.…”
Section: Coexistence Of Genetic and Environmental Influencessupporting
confidence: 50%
“…Altogether, these recent data confirmed that at least in these lineages TSD and GSD are not mutually exclusive systems but the 2 extreme endpoints of a continuum, underlying the coexistence of both genetic and environmental influences in the middle of this spectrum: 'many species have differentiated sex chromosomes, but also show a temperature override, where genes and environment interact to determine sex' [Holleley et al, 2015]. In fact just recently, a three-ended continuum that can be visualized as a triangle has been proposed [Perrin, 2016] in which genes, environment, and random factors (i.e., any stochastic fluctuation in the expression of key genes of the cascade) could interact to determine sex.…”
Section: Coexistence Of Genetic and Environmental Influencessupporting
confidence: 50%
“…Furthermore, the coexistence of multiple sex determining loci in a number of species (e.g., cichlids, housefly, zebrafish, seabass) suggests that multifactorial sex determination need not be unstable, provided the sex ratio is balanced (Liew et al, ; Meisel et al, ; Moore & Roberts, ; Roberts et al, ; Vandeputte, Dupont‐Nivet, Chavanne, & Chatain, ; Wilson et al, ). Because sex operates as a threshold trait in which female or male development is triggered when genetic and/or environmental cues surpass some level (Bulmer & Bull, ; Roff, ), the presence of multiple sex determining loci may not necessarily indicate that a system is undergoing a sex chromosome turnover (Beukeboom & Perrin, ; Perrin, ; Rodrigues et al, ).…”
Section: Future Directions and Perspectivesmentioning
confidence: 99%
“…However, the female versus hermaphrodite decision could also be modulated by environmental cues acting during embryogenesis and the L1 stage. These maternal and environmental effects could be modulations of what is essentially a random sex determination (RSD) system [85]. RSD occurs when fluctuations in the expression of genes at the top of the sex determining cascade or "developmental noise" are enough to canalise sexual fate down contrasting paths.…”
Section: Discussionmentioning
confidence: 99%